2016
DOI: 10.1186/s40623-016-0545-7
|View full text |Cite|
|
Sign up to set email alerts
|

Fault source model for the 2016 Kumamoto earthquake sequence based on ALOS-2/PALSAR-2 pixel-offset data: evidence for dynamic slip partitioning

Abstract: Series of earthquakes including three M w > 6 earthquakes occurred in Kumamoto prefecture in the middle of the Kyushu island, Japan. In order to reveal the associated crustal deformation signals, we applied offset tracking technique to ALOS-2/PALSAR-2 data covering three M w > 6 earthquakes and derived the 3D displacements around the epicenters. We could identify three NE-SW trending displacement discontinuities in the 3D displacements that were consistent with the surface location of Futagawa and Hinagu fault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
68
2

Year Published

2017
2017
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 28 publications
(16 reference statements)
11
68
2
Order By: Relevance
“…Several source models of the Mj7.3 of the 2016 Kumamoto earthquake have been proposed on the basis of the Open Access *Correspondence: yoshida@geor.or.jp 1 Geo-Research Institute, 2-1-2 Otemae, Chuo-ku, Osaka 540-0008, Japan Full list of author information is available at the end of the article strong motions (e.g., Asano and Iwata 2016), teleseismic waveforms (Yagi et al 2016), and crustal deformation (e.g., Himematsu and Furuya 2016). Most of these studies based on seismic data assume northwest-dipping fault planes.…”
Section: Introductionmentioning
confidence: 99%
“…Several source models of the Mj7.3 of the 2016 Kumamoto earthquake have been proposed on the basis of the Open Access *Correspondence: yoshida@geor.or.jp 1 Geo-Research Institute, 2-1-2 Otemae, Chuo-ku, Osaka 540-0008, Japan Full list of author information is available at the end of the article strong motions (e.g., Asano and Iwata 2016), teleseismic waveforms (Yagi et al 2016), and crustal deformation (e.g., Himematsu and Furuya 2016). Most of these studies based on seismic data assume northwest-dipping fault planes.…”
Section: Introductionmentioning
confidence: 99%
“…The inferred models suggest that the M JMA 7.3 event started near the intersection of the Futagawa and Hinagu faults by right-lateral strike-slip movement; then, the rupture propagated to the NE along the Futagawa fault as strike-slip with a normal faulting component. Finite source models and also static slip models from geodetic data (Himematsu and Furuya 2016;Fukahata and Hashimoto 2016) are consistent with field measurements of co-seismic surface ruptures. The source models introduce two or three segments of the mainshock rupture, but their physical relation to the foreshock ruptures remains unclear because of the complex tectonic settings of the intersection of the Futagawa and Hinagu faults.…”
Section: Introductionmentioning
confidence: 51%
“…Co-activation of the right-lateral strike-slips with normal faulting ruptures through the sequence was introduced also by static slip model from geodetic data (Himematsu and Furuya 2016;Kobayashi 2017). Field investigation by Toda et al (2016) shows that surface displacements along the previously mapped active fault traces of the Hinagu-Futagawa fault zone are dominated by right-lateral strike-slip surface displacement up to 2 m. A normal surface rupture zone of about 10 km in length dipping to northwest, which is parallel to the Futagawa fault outside the Aso caldera, was also reported by Toda et al (2016), and its maximum co-seismic displacement is also up to 2 m. The normal dip-slip aftershocks that occurred along the NW edge of the mainshock rupture had no clear relationship with co-seismic surface ruptures; however, minor surface ruptures in downtown of Kumamoto City have been mapped by InSAR (Himematsu and Furuya 2016) and field survey (Goto et al 2017).…”
Section: Solutions In Seismotectonic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the data from ALOS-2, several groups present models of coseismic deformation on faults. Himematsu and Furuya (2016) exploit pixel offsets as well as phase changes to reveal deformation. Ozawa et al (2016) present a model with four fault segments by fitting the observed interferograms of ALOS-2.…”
mentioning
confidence: 99%